Cidades sustentáveis e competitivas: contribuições do desenvolvimento urbano sustentável para a atratividade dos municípios - Costa, Carlos Rafael Röhrig da (2019)
Population concentration in urban centers has been a striking feature of the world development process. The accelerated growth of cities is often confused with development; however, in parallel with the benefits, these spaces have brought negative impacts. Thus, it is increasingly necessary to plan more sustainable cities, which may favor cities to present themselves, among other aspects, more attractive for the collection of resources. Based on these considerations, the challenge arises of understanding the relationship between sustainable urban development and urban competitiveness. The problem of this research, thus defined: What is the relationship between sustainable urban development and urban competitiveness? The present work is quantitative research with secondary data and aims to contribute to inferences about the relationship between sustainable urban development and the degree of competitiveness of cities, through statistical analyzes such as descriptive statistics, bivariate correlation, and multiple regression. The analyzes made possible the achievement of the objectives of its application since it allowed the identification of sustainable urban development in the urban competitiveness of the cities surveyed. It also made it possible to achieve the specific objectives of this research, since it was verified characteristics of sustainable urban development and aspects of urban competitiveness present in the cities analyzed. It was also analyzed the influence of the size of municipalities on sustainable urban development and urban competitiveness. It should be emphasized that the present study had as its central objective to verify the relationship between sustainable urban development and the urban competitiveness of the analyzed municipalities, which could be observed through bivariate correlation and multiple regression analyses. The correlation analysis verified the association between the dimensions of sustainable urban development and urban competitiveness. It is possible to emphasize that aspects considered as a result of practices aimed at sustainable urban development reflect in results that serve to favor the urban competitiveness of these municipalities. Finally, the regression analysis confirmed the relationship between sustainable urban development and urban competitiveness. From the results, it can be affirmed that urban competitiveness is influenced by sustainable urban development, which reinforces the association previously verified in the correlation analysis. The results show that, in particular, the 'Environmental', 'Political-Institutional' and 'Cultural' dimensions significantly influence the urban competitiveness of the cities surveyed.